Determining the visual preference of urban landscapes - Abkar, Mahdieh; Mohd Shariff, Mustafa Kamal; Maulan, Suhardi; Davoodi, Seyed Rasoul (Academic Journals, 2011)
This study attempted to determine people’s visual preference for urban landscapes in Malaysia. In an experimental study, 120 students from three departments in Universiti Putra Malaysia rated 4 predictors of preference (Coherence, complexity, legibility and mystery) and a criterion variable (preference) of 24 color slides depicting urban built landscape (UBL) and urban natural landscape (UNL) scenes. The results of this study showed that the mean preference and the four predictor ratings were significantly higher for UNL than UBL and it confirmed the role of urban nature in urban landscapes. Also, the results showed that all the predictors of preference could explain a large amount of variance in preference, except for “legibility” in UBL. “Mystery” and “complexity” are found to be the most influential predictors of preference in both categories. Furthermore, “coherence” in UNL notably predicts more preference than in UBL. However, knowledge about preferences and the characteristics of urban landscapes contributes to the designing of an enjoyable environment by designers or planners, and to the decision makers who manage the landscape settings for their users.